Facile Synthesis of Unusual Pyrimidine Nucleosides - Singh Yadava, Virendra (Asian Journal of Chemistry, 2010)
Two novel unusual pyrimidine nucleosides, viz., 1-(2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl)- 5-iodo-6-methyluracil (1) and 1-(2,3,4,6-tetra-O-acetyl-β-D-galactopyranosyl)-5-iodo- 6-methyluracil (2) have been prepared using HgCl2/TiCl4 method and characterized.